2021
DOI: 10.1097/bsd.0000000000001247
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Is Associated With Lower Satisfaction in Nondiabetic Patients Undergoing Minimally Invasive Single-level Transforaminal Lumbar Interbody Fusion

Abstract: This was a retrospective review of prospectively collected registry data.Objective: The objective of this study was to investigate the effect of smoking on 2 years postoperative functional outcomes, satisfaction, and radiologic fusion in nondiabetic patients undergoing minimally invasive transforaminal lumbar interbody fusion (TLIF) for degenerative spine conditions. Summary of Background Data:There is conflicting data on the effect of smoking on long-term functional outcomes following lumbar fusion. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…9,10 Although minimally invasive (MIS) TLIF has been associated with lower blood loss, length of hospitalization and tissue injury than open TLIF, previous studies have shown that both groups of patients achieve comparable clinical and functional outcomes in the long-term 11,12 Several preoperative factors may contribute to poor postoperative outcomes after spine surgery, including smoking, poor preoperative neurological status, and a longer duration of symptoms. [13][14][15] Several perioperative factors such as longer operative duration, longer hospitalization duration, surgical complications and need for revision surgery have also been shown to affect postoperative TLIF outcomes. 16,17 However, there remains a paucity of literature regarding the factors affecting PROMs and attainment of MCID following lumbar fusion, despite the growing recognition of their importance.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Although minimally invasive (MIS) TLIF has been associated with lower blood loss, length of hospitalization and tissue injury than open TLIF, previous studies have shown that both groups of patients achieve comparable clinical and functional outcomes in the long-term 11,12 Several preoperative factors may contribute to poor postoperative outcomes after spine surgery, including smoking, poor preoperative neurological status, and a longer duration of symptoms. [13][14][15] Several perioperative factors such as longer operative duration, longer hospitalization duration, surgical complications and need for revision surgery have also been shown to affect postoperative TLIF outcomes. 16,17 However, there remains a paucity of literature regarding the factors affecting PROMs and attainment of MCID following lumbar fusion, despite the growing recognition of their importance.…”
Section: Introductionmentioning
confidence: 99%